An efficient power management technique for data centres using smart grid. (2016) - Nageswari, M.K.; Reddy, T. Sunil Kumar
The cloud computing is treated as one of the emerging fields in distributed systems. The major concern about cloud computing is that it has to maintain massive data centres, which contains thousands of computer servers and requires huge amount of energy. This huge amount of energy consumption will directly impact the power grid by increasing the load at the generations. To attain some solution to this problem, we developed a mechanism called as power management in cloud computing to efficiently manage the power in a smart grid environment. This mechanism analysed how cloud and smart grid can be related to this issue. Simulation results show the proposed system in cloud computing is helpful for a smart grid to balance their loads and also for building a reliable network.